2005
DOI: 10.1002/jbm.b.30235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of filler composition on flexibility of microfilled resin composite

Abstract: The effects of the filler composition on physical and mechanical properties of microfilled composites was investigated by measuring water absorption, solubility, compressive, flexural, and impact strength. A series of experimental composites, consisting of UDMA/TEGDMA comonomer matrix and prepolymerized fillers, was fabricated. The prepolymerized fillers were composed of hydrophobic colloidal silica and two monomers in varying ratios, trimethylolpropanetrimethacrylate (TMPT), and polyesterdiacrylate (PEDA). TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Several changes occur to resin-based composites during the aging process that can influence the success of the repairing procedure, such as water sorption, chemical degradation, and leaching out of some constituents [6,36,37]. On this account, the age of the restoration to be repaired plays a fundamental role in the bond strength of composite repairs [18].…”
Section: Discussionmentioning
confidence: 99%
“…Several changes occur to resin-based composites during the aging process that can influence the success of the repairing procedure, such as water sorption, chemical degradation, and leaching out of some constituents [6,36,37]. On this account, the age of the restoration to be repaired plays a fundamental role in the bond strength of composite repairs [18].…”
Section: Discussionmentioning
confidence: 99%
“…5,9 In the mouth, absorption of water by diffusion through the resin phase of composites will affect the ability of the new composite to adhere to the aged composite, because the number of available unsaturated double bonds diminishes with aging. 10 The shear bond strength (SBS) of fresh composite to the composite aged in water or contaminated with artificial saliva has been studied previously. [11][12][13] In these studies, various methods have been suggested for establishing satisfactory SBS levels between the existing composite and the fresh one: mechanical grinding, acid etching, resin coating, or a combination of these treatments.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Several changes occur to resin-based composites during aging process which could influence of the success of repairing procedure such as water sorption, chemical degradation and leaching out of some their constituents. [5][6][7] If adequate bonding between the old resinbased composite and freshly added bonding resin could be achieved, the repair of the existed old restorations becomes an attractive solution. 4 Many researches [8][9][10][11] studied the relevance of various chemical and/or mechanical treatments of aged resin-based composites on the repair bond strength.…”
Section: Introductionmentioning
confidence: 99%